Synthesis and structural depiction of the isomeric benzimidazole pair and its in-silico anti-SARS-CoV-2 activities - Debnath, Ananya; Mahato, Shreya; De, Abhranil; Verma, Himanshu; Silakari, Om; Biswas, Bhaskar (European Journal of Chemistry, 2024)
The present work presents a straightforward synthesis, spectroscopic and structural depiction, and in silico anti-SARS-CoV-2 activity of an isomeric monosubstituted benzimidazole pair, 2-(1H-benzo[d]imidazol-2-yl)-6-methoxyphenol (L1O) and 4-(1H-benzo[d]imidazol-2-yl)-2-methoxyphenol (L1P). The derivatives were synthesized by a coupling of aromatic aldehydes and o-phenylenediamine in ethanol under reflux. Different spectroscopic methods and X-ray structural analysis were employed to characterize the compounds. The crystal structure of L1O reveals that the o-vanillin substituted benzimidazole compound crystallizes in a monoclinic system and adopts a planar geometry. In silico anti-SARS-CoV-2 proficiencies of synthetic derivatives were evaluated against the main protease (Mpro) and nonstructural proteins (nsp2 and nsp7) of SARS-CoV-2. Molecular docking reveals the binding scores for the L1O-Mpro, L1O-nsp2 and L1O-nsp7 complexes as -11.31, -6.06 and -8.13 kcal/mol, respectively, while the binding scores for the L1P-Mpro, L1P-nsp2 and L1P-nsp7 complexes as -10.62, -5.09 and -6.91 kcal/mol, respectively, attributing the excellent conformational stability for both the isomeric benzimidazole derivatives.